Dry powder coating in additive manufacturing - Schmidt, Jochen; Peukert, Wolfgang (Frontiers in Chemical Engineering, 2022)
Dry powder coating is used in many industries to tailor the bulk solid characteristics of cohesive powders. Within this paper, the state of the art of dry coating of feedstock materials for powder based additive manufacturing (AM) processes will be reviewed. The focus is on feedstock materials for powder bed fusion AM processes, such as powder bed fusion of polymers with a laser beam and powder bed fusion of metals with lasers or an electron beam. Powders of several microns to several ten microns in size are used and the feedstock’s bulk solid properties. Especially the flowability and packing density are of immanent importance in different process steps in particular for powder dosing and spreading of powder layers onto the building area. All these properties can be tuned by dry particle coating. Moreover, possibilities to improve AM processability and to manipulate the resulting microstructure (c.f. grain refinement, dispersion strengthening) by adhering nanoparticles on the powders will be discussed. The effect of dry coating on the obtained powder properties along the whole AM process chain and the resulting part properties is assessed. Moreover, appropriate characterization methods for bulk solid properties of dry-coated AM powders are critically discussed.